Experimental Evaluation of Performance and Combustion Characteristics in a Hydrogen-Methane Port Fueled Diesel Engine at Different Compression Ratios - YILMAZ, İLKER TURGUT; GÜMÜŞ, METİN (AMER CHEMICAL SOC, 2020)
This paper investigates the performance and combustion characteristics of a common-rail diesel engine fueled with methane and hydrogen enrichment of methane under different loads (2.15, 4.3, 6.45, and 8.6 bar) and compression ratios (CRs) (18.25, 16.9, and 15.8). Traditional diesel fuel is used as the pilot fuel and is injected twice as pre- and main injections. Results of the usage of gaseous fuels are compared with each other and the single diesel mode. Accordingly, brake thermal efficiency (BTE) and brake specific energy consumption (BSEC) are highly deteriorated at low loads, but they improve with load. Hydrogen substitution results in slightly higher BTE and lower BSEC. The average exhaust temperature with gaseous fuels is enhanced compared to that with diesel. Peak cylinder pressures of dual-fuel operations are higher, and an earlier heat release is observed; moreover, combustion noise of dual-fuel operations is further enhanced under a high CR-high load condition. Finally, combustion durations substantially change with loads and CRs.
Keywords: DUAL-FUEL; NATURAL-GAS; EMISSION CHARACTERISTICS; IGNITION ENGINE; METHYL-ESTER; PILOT INJECTION; SI ENGINE; BIOGAS; CNG; MIXTURES